Fashion Jilbab di Kalangan Mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan UIN Sumatera Utara - Nasution, Abdul Gani Jamora; Hafza, Abyena; Juliani, Afrida; Adeana, Fadillah Putri; Harahap, Hasima; Rizky, Putri (AHKAM, 2022)
This article examines “Hijab Fashion Among Students of the Tarbiyah and Teacher Training Faculty of UIN North Sumatra” using a descriptive qualitative approach. focus on answering the first question, about female students' understanding of the headscarf. Second, regarding the reference to the hijab style. Third, regarding the trend of wearing the headscarf and regulations in the Faculty of Tarbiyah Science and Teacher Training at UIN North Sumatra Medan. The results of the study show that first, when critically discussed, a fundamental difference is found regarding the understanding of the headscarf for women. Second, the style or model of wearing the hijab for female students at the State Islamic University of North Sumatra, especially the Faculty of Tarbiyah and Teacher Training, varies greatly. The change of every hijab model trend cannot be separated from the influence of social media, such as Instagram, Tiktok, YouTube. Third, there are several classification models for the trend of wearing the headscarf when compared to FITK regulations, namely that only a few female students cover their genitals, such as covering their chests, clothes that are not too thin, tight, and cover their genitals up to their wrists, which follow the hijab rules according to FITK regulations. However, there are also not a few female students who do not follow the hijab rules according to FITK regulations.